The Urgency of Audio-Visual Media in Arabic Language Learning: A Systematic Literature Review - Ahmad Tarmizi; Fielga Permata Sari (The Progress: Journal of Language and Ethnicity, 2023)
Learning media can be used to stimulate the learning motivation of students, ultimately enhancing their problem-solving abilities. This study aims to conduct a literature review regarding the importance of audio-visual media in Arabic language learning within secondary schools. The research method employed in this study is Systematic Literature Review (SLR). Data collection was carried out by documenting all articles related to similar research in this research report. Based on this study, it was found that audio-visual media significantly improves students' understanding of the Arabic language. Therefore, the implementation of such media is deemed urgent considering the increasing gap between learners and advancing technology.